2018
DOI: 10.3390/cancers10100353
|View full text |Cite
|
Sign up to set email alerts
|

Destruxin B Suppresses Drug-Resistant Colon Tumorigenesis and Stemness Is Associated with the Upregulation of miR-214 and Downregulation of mTOR/β-Catenin Pathway

Abstract: Background: Drug resistance represents a major challenge for treating patients with colon cancer. Accumulating evidence suggests that Insulin-like growth factor (IGF)-associated signaling promotes colon tumorigenesis and cancer stemness. Therefore, the identification of agents, which can disrupt cancer stemness signaling, may provide improved therapeutic efficacy. Methods: Mimicking the tumor microenvironment, we treated colon cancer cells with exogenous IGF1. The increased stemness of IGF1-cultured cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…It has been reported that the mTOR signaling pathway can induce colon cancer tumorigenesis (29). Furthermore, several studies have showed that antitumor effects can be enhanced by inhibiting mTOR signaling pathway in colon cancer cells (30,31). Similarly, our results showed that Shikonin induced colon cancer cell apoptosis by down-regulating activation of mTOR signaling.…”
Section: Discussionsupporting
confidence: 76%
“…It has been reported that the mTOR signaling pathway can induce colon cancer tumorigenesis (29). Furthermore, several studies have showed that antitumor effects can be enhanced by inhibiting mTOR signaling pathway in colon cancer cells (30,31). Similarly, our results showed that Shikonin induced colon cancer cell apoptosis by down-regulating activation of mTOR signaling.…”
Section: Discussionsupporting
confidence: 76%
“…We conducted a population-based cohort study using Taiwan National Health Insurance (NHI) Research Data (NHIRD) linked to the TCRD. The TCRD was established in 1979 and contains 97% of the cancer cases in Taiwan [ 13 ]. The NHIRD includes all medical claims data on disease diagnoses, procedures, drug prescriptions, demographics, and enrollment profiles of all beneficiaries [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…miR-214 was frequently reported to be a tumor suppressive miRNA ( Wu et al, 2018 ; Karimkhanloo et al, 2020 ). Here, we found that SPINT1-AS1 and miR-214 reciprocally repressed each other.…”
Section: Resultsmentioning
confidence: 99%
“…The critical oncogenic protein β-catenin was a well-known miR-214 downstream target ( Wu et al, 2018 ; Karimkhanloo et al, 2020 ). Given that SPINT1-AS1 exerts oncogenic roles in cervical cancer via binding DNM3OS and repressing miR-214 biogenesis, we further explored the potential roles of SPINT1-AS1 on Wnt/β-catenin signaling.…”
Section: Resultsmentioning
confidence: 99%